Angiographic and clinical outcomes of balloon remodeling versus unassisted coil embolization in the ruptured aneurysm cohort of the GEL THE NEC study. (18th August 2017) - Dabus, Guilherme; Brinjikji, Waleed; Amar, Arun P; Delgado Almandoz, Josser E; Diaz, Orlando M; Jabbour, Pascal; Hanel, Ricardo; Hui, Ferdinand; Kelly, Michael; Layton, Kennith F; Miller, Jeffrey W; Levy, Elad I; et al.
Abstract : Background and purpose: GEL THE NEC (GTN) was a multicenter prospective registry developed to assess the safety and efficacy of HydroSoft coils in treating intracranial aneurysms. We compared the angiographic and clinical outcomes of aneurysms treated with balloon assisted coil embolization (BACE) versus unassisted coil embolization (CE) in the ruptured aneurysm cohort. Materials and methods: GTN was performed at 27 centers in five countries. Patients aged 21–90 years with a ruptured aneurysm 3–15 mm in size were eligible for enrollment. We analyzed demographics/comorbidities, aneurysm location, and geometry, including maximum diameter, neck size, and dome to neck ratio, immediate and long term angiographic outcomes (graded by an independent core laboratory using the modified Raymond Scale), and procedure related adverse events. Angiographic and clinical outcomes were studied using χ 2 and t tests. Results: Of the 599 patients in the GTN, 194 met the inclusion criteria. 84 were treated with BACE and 110 with CE. There were more prior smokers in the BACE group (p=0.01). The BACE group also had more vertebrobasilar aneurysms (p=0.006) and a larger mean neck size (p=0.02). More aneurysms were immediately completely occluded in the BACE group (p=0.02) Procedure- related major morbidity and mortality were no different between the techniques (p=0.4 and p=1, respectively). Conclusions: In this prospective ruptured aneurysm cohort from the GTN, BACE resulted in greater occlusion rates compared with unassisted CE with similar morbi-mortality.